Women who hate men: a comparative analysis across extremist Reddit communities - Erica Coppolillo (Scientific Reports)
Abstract In the present online social landscape, while misogyny is a well-established issue, misandry remains significantly underexplored. In an effort to rectify this discrepancy and better understand the phenomenon of gendered hate speech, we analyze four openly declared misogynistic and misandric Reddit communities, examining their characteristics at a linguistic, emotional, and structural level. We investigate whether it is possible to devise substantial and systematic discrepancies among misogynistic and misandric groups when heterogeneous factors are taken into account. Our experimental evaluation shows that no systematic differences can be observed when a double perspective, both male-to-female and female-to-male, is adopted, thus suggesting that gendered hate speech is not exacerbated by the perpetrators’ gender, indeed being a common factor of noxious communities.